2017
DOI: 10.1002/ece3.3254
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of the first 2 years of industry‐led badger culling in England on the incidence of bovine tuberculosis in cattle in 2013–2015

Abstract: Culling badgers to control the transmission of bovine tuberculosis (TB) between this wildlife reservoir and cattle has been widely debated. Industry‐led culling began in Somerset and Gloucestershire between August and November 2013 to reduce local badger populations. Industry‐led culling is not designed to be a randomized and controlled trial of the impact of culling on cattle incidence. Nevertheless, it is important to monitor the effects of the culling and, taking the study limitations into account, perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…Results from the four area badger removal trial in Ireland and the Randomized Badger Culling Trial (RBCT) in England provided evidence of a positive effect of badger culling on incidence rates of tuberculosis in associated cattle herds ( 18 , 19 ). Arising from these studies, current policies to eradicate the disease are largely focused on surveillance testing of cattle supplemented with badger population control measures in areas of Ireland and England considered as high risk for cross-species transmission ( 1 , 20 ). Analysis of M. bovis prevalence rates in approximately 5,000 badgers culled in Ireland in response to tuberculosis breakdowns in cattle herds has revealed a decrease in the overall prevalence from 26 to 11% between 2007 and 2011 ( 21 ).…”
Section: Tuberculosis In Badgersmentioning
confidence: 99%
“…Results from the four area badger removal trial in Ireland and the Randomized Badger Culling Trial (RBCT) in England provided evidence of a positive effect of badger culling on incidence rates of tuberculosis in associated cattle herds ( 18 , 19 ). Arising from these studies, current policies to eradicate the disease are largely focused on surveillance testing of cattle supplemented with badger population control measures in areas of Ireland and England considered as high risk for cross-species transmission ( 1 , 20 ). Analysis of M. bovis prevalence rates in approximately 5,000 badgers culled in Ireland in response to tuberculosis breakdowns in cattle herds has revealed a decrease in the overall prevalence from 26 to 11% between 2007 and 2011 ( 21 ).…”
Section: Tuberculosis In Badgersmentioning
confidence: 99%
“…There will also be confounding factors that affect the cull duration required to reduce disease levels. For example, Brunton et al [52] found that badger culling led to a reduction in bTB levels (in sympatric cattle) after 2 years of culling, but partly attributed this to the implementation of an additional risk management programme in the second year of disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Smith 2002). The control of badger populations by culling has been shown to reduce the incidence of bTB in cattle inside the culling areas (Brunton et al 2017;Jenkins et al 2010). However, culling disrupts the local badger population structure, and remaining animals tend to move longer distances and visit neighbouring social groups more frequently (Carter et al 2007;R.…”
Section: Introductionmentioning
confidence: 99%